Anti-inflammatory effects of Artemisia stechmanniana Besser extract on LPS-stimulated macrophages. Issue 1 (1st January 2021) - Kim, Wan-Hoon; Jang, Hyun Jun; Kim, Jisu; Jeong, Chi Hwan; Enebish, Ganbold; Kim, Soo-Yong; Min, Hyeyoung
ABSTRACT: A. stechmanniana Besser is a semi-shrub plant indigenous to Mongolia, Central Asia, Russia, and Pakistan. Although A. stechmanniana has been used as folk medicine for inflammation, helminth infection, and tumors, the physiological activities of A. stechmanniana have not been fully experimentally validated. We investigated the anti-inflammatory activities and underlying mechanisms of action of A. stechmanniana on LPS-stimulated murine macrophages. Macrophages treated with A. stechmanniana -methanol extract (As-ME) showed the decreased expression of inducible NO synthase and cyclooxygenase-2 and secretion of NO, prostaglandin E2, and pro-inflammatory cytokines. Furthermore, we found As-ME reduced the phosphorylation of c-Jun N-terminal kinase (JNK), which was accompanied by a decrease in c-Jun in the nucleus, and suppressed the phosphorylation of NF-κB inhibitor α and the translocation of NF-κB into the nucleus. The results indicated that As-ME possesses anti-inflammatory effects mediated through inhibition of JNK and NF-κB phosphorylation.